Prospective plasma efavirenz concentration assessment in Chinese HIV‐infected adults enrolled in a large multicentre study1. Issue 7 (15th May 2018) - Guo, F; Cheng, X; Hsieh, E; Du, X; Fu, Q; Peng, W; Li, Y; Song, X; Routy, J‐P; Li, T
Abstract : Objectives: Few studies have explored the optimal dosing for efavirenz in individuals from China. We investigated plasma efavirenz concentrations and their association with efficacy and tolerance of efavirenz 600 mg daily in Chinese HIV‐infected adults. Methods: An analysis was performed using plasma samples from 455 patients enrolled in a prospective multicentre trial in China. A total of 1198 plasma samples collected at weeks 4, 24 and 48 following antiretroviral therapy initiation were analysed. The mid‐dose interval efavirenz concentrations ( C 12 ) were determined using high‐performance liquid chromatography. Results: The median efavirenz concentration (interquartile range) steadily increased over time from 3.02 (2.28–4.23) to 3.71 (2.91–4.91) mg/L from week 4 to 48 ( P < 0.001). The proportion of patients with C 12 > 4.0 mg/L also rose from 28.0% to 34.2% and 43.8%, measured at 4, 24 and 48 weeks, respectively ( P < 0.001). Five patients had efavirenz concentrations < 1.0 mg/L at week 4, 24 or 48. In the multivariable regression analysis, lower body weight and non‐Han ethnicities were associated with higher efavirenz concentrations over time. At each time‐point, patients with a body weight < 60 kg had significantly higher efavirenz C 12 compared with those with body weight ≥ 60 kg ( P < 0.05). Conclusions: Efavirenz concentrations increased steadily over 48 weeks, and a substantial proportion of participants had efavirenz C 12 above the upper limit of the proposed therapeutic window, especially those with low body weight (< 60 kg). Based upon these findings, a dosage reduction of efavirenz to 400 mg daily may warrant consideration in this population, especially for those with lower body weight.